Filipino Women Taking on Their Endangered, Engendered World - Ballescas, Maria Rosario Piquero (Review of Women's Studies; Vol 14 No 2 (2004): Review of Women's Studies Volume XIV, Number 2 (July-December 2004))
This article aims to: 1) show the endangered, engendered world of the Filipino women and discuss the role of globalization in the continuation of this endangered, engendered world, and most importantly, 2) highlight the responses of Filipino women to this historically continuing world of burden. It cites statistics from the United Nations and the offices of the Philippine government to validate its position.